Knowledge and Self-Practice of Pharmacists and Prescribers Towards The Uses of Generic Drugs In Community Settings in Belagavi, Karnataka, INDIA - Rashmilata, Rawat; Shivakantayya, Ganachari Madiwalayya; Geetanjali, Salimath (Indian Journal of Pharmacy Practice)
Background: To increase the knowledge of health professionals towards generic drugs so that they increase the practice of using generic drugs in their daily routine. Aims: To evaluate/investigate the Knowledge and selfpractice of Pharmacists, Prescribers regarding Generic Drug (GD) Use. Settings and Design: A community based quasi experimental study. Methods and Material: Validated Pre self-administered questionnaires for Pharmacists and Physicians were prepared. In between educational workshop and Information leaflet were provided. Post questionnaires were given to both health professionals and consumers to assess their awareness and were asked to answer the questionnaires’ used during pre-survey. Data was collected by completing the informative questionnaires. Statistical Analysis: Scores were analysed using software SPSS, version 30.0. Results: 183 Physicians and Pharmacists were participated, 146 were community pharmacists and 37 were physicians. 125 (85.62%) pharmacists, 31 (83.78%) physicians were believed that GDs are therapeutically bio equivalent to innovator drugs. 123 (84.24%) Pharmacists, 25 (67.57%) physicians agreed that GDs contain the same active ingredients and treat the same disease at the same dose compare to brand name drug. Among the participants, 127 (86.99%) pharmacists have stored GDs at their stores. Majority of 37 physicians preferred prescribing GDs. Conclusions: This study, Knowledge and self-practice of Pharmacists and Prescribers towards the uses of Generic drugs in community settings found acceptable awareness among general population that reduces the cost of health expenditure and improves quality of life. The counselling and education improved the perception of pharmacists and prescribers towards Generic drug use.
Keywords: Knowledge; Practice; Health professionals; Generic drugs; Pharmacists; Prescribers; Community